Preparation and evaluation of a novel sunflower oil‐based waterborne polyurethane nanoparticles for sustained delivery of hydrophobic drug. Issue 8 (27th March 2017) - Omrani, Ismail; Babanejad, Niloofar; Shendi, Hasan Kashef; Nabid, Mohammad Reza
Abstract : In the present study, a nanoparticulate system based on bio‐based waterborne polyurethane for the controlled delivery of raloxifene‐hydrochloride, as a model and drug with poor bioavailability, is described and considered to be an antiproliferative agent of mammary tissue. The main goal of this study was to investigate the effect of the encapsulation of raloxifene in bio‐based polyurethane, synthesized for the first time, as a polymer with anionic surface on the release profile as well as antiproliferative activity. Polyurethane was synthesized from bio‐based polyol, which was derived from sunflower oil. The structure of bio‐based polyurethane was characterized using 1 HNMR, FT‐IR, and TGA. Drug release studies showed controlled release of raloxifene from anionic nanoparticles that was mainly driven by diffusion‐based mechanism. Degradation of nanoparticles during the release of Ral was investigated applying SEM and caused mainly through the hydrolysis of polyurethane. MCF‐7 cell viability studies demonstrated that, raloxifene loaded nanoparticles promote the antiproliferative activity after 72 h of treatment. The bio‐based polyurethane has potential as a useful carrier for controlled release of hydrophobic drugs. Practical applications : A novel carboxylic acid group containing polyol was prepared from sunflower oil and used in preparation of biodegradable waterborne polyurethane. The synthesized waterborne polyurethane was loaded by drug and its loading capacity was studied. Drug release studies showed controlled release of raloxifene from anionic nanoparticles that was mainly driven by diffusion‐based mechanism. Cell viability studies demonstrated that raloxifene loaded nanoparticles promote the antiproliferative activity. A novel carboxylic acid group containing polyol was prepared from sunflower oil and used in preparation of biodegradable waterborne polyurethane. The synthesized waterborne polyurethane was loaded by drug and its loading capacity was studied. Drug release studies showed controlled release of raloxifene from anionic nanoparticles that was mainly driven by diffusion‐based mechanism. Cell viability studies demonstrated that raloxifene loaded nanoparticles promote the antiproliferative activity. Abstract : A novel carboxylic acid group containing polyol was prepared from sunflower oil and used in preparation of biodegradable waterborne polyurethane. The synthesized waterborne polyurethane was loaded by drug and its loading capacity was studied. Drug release studies showed controlled release of raloxifene from anionic nanoparticles that was mainly driven by diffusion‐based mechanism. Cell viability studies demonstrated that raloxifene loaded nanoparticles promote the antiproliferative activity.